Place-Based Industrial Policies and Local Agglomeration in the Long Run - Lorenzo Incoronato; Salvatore Lattanzio (CESifo GmbH, 2024)
This paper studies a place-based industrial policy (PBIP) aiming to establish industrial clusters in Italy in the 1960s-70s. Combining historical archives spanning one century with administrative data and leveraging exogenous variation in government intervention, we investigate both the immediate effects of PBIP and its long-term implications for local development. We document agglomeration of workers and firms in the targeted areas persisting well after the end of the policy. By promoting high-technology manufacturing, PBIP favored demand for business services and the emergence of a skilled local workforce. Over time, this produced a spillover from manufacturing – the only sector targeted by the program – to services, especially in knowledge-intensive jobs. Accordingly, we estimate higher local wages, human capital, and house prices in the long run. We provide suggestive evidence that these persistent effects may depend on the initial conditions of targeted locations.
Keywords: J24; N94; O14; O25; R58; 330; place-based industrial policy; employment; wages; agglomeration